The chemical synthesis of human milk oligosaccharides: lacto-N-tetraose (Galβ1→3GlcNAcβ1→3Galβ1→4Glc) - Bandara, Mithila D. (Carbohydr Res, 2019)
The total chemical synthesis of lacto-N-tetraose (LNT) has been completed using both convergent and linear strategies. Similarly to that of our previous HMO syntheses, the donor-acceptor protecting-leaving group combinations were found to be of paramount significance to achieving successful glycosylations and minimizing side reactions.